Quantification of xylooligomers in hot water wood extract by 1H–13C heteronuclear single quantum coherence NMR. (6th March 2015) - Yan, Jipeng; Kiemle, David; Liu, Shijie
Highlights: A new method is developed to quantify xylo-oligomers in hot water extract. Acetylated xylo-units has the different 2D-HSQC resonance response. The new method compare fairly with data after hydrolysis. Abstract: A new method that employs 2D-HSQCNMRwasdeveloped to determine xylooligomer concentrations in the hot water extracts of Paulownia elongata, aspen, sugar maple, southern hardwood mixture, and willow woodchips. Equations for computing oligomer concentrations calculation were developed based on HSQC corresponding resonance integrals of xylooligomer C1 H1 and monomeric sugar standard curves. The degree of polymerization ( DP ) of xylooligomers in the hot water extract was computed by equation obtained from a series of xylooligomer standard solutions with DP s that ranged from 2 to 6. Another group of hot water wood extract that is served as a control group was hydrolyzed by 4% sulfuric acid at 121 °C for 60 min in order to convert all xylooligomer into xylose. As 2D-HSQC resonance response is different for acetylated xylo-units, as compared with non-acetylated units, proton NMR was used to calibrate the acetylated xylooligomer concentration. Xylooligomer concentrations determined from HSQC compared fairly well with data after hydrolysis.